2002
DOI: 10.1042/bj20020058
|View full text |Cite
|
Sign up to set email alerts
|

Size is a major determinant of dissociation and denaturation behaviour of reconstituted high-density lipoproteins

Abstract: Lipid-free apolipoprotein A-I (apoA-I) and A-I(Milano) (A-I(M)) were compared for their denaturation behaviour by running across transverse gradients of a chaotrope, urea, and of a ionic detergent, SDS. For both apo A-I and monomeric apoA-I(M) in the presence of increasing concentrations of urea the transition from high to low mobility had a sigmoidal course, whereas for dimeric A-I(M)/A-I(M) a non-sigmoidal shape was observed. The co-operativity of the unfolding process was lower for dimeric A-I(M)/A-I(M) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A number of groups have investigated the spontaneous remodeling of apoA-I-based rHDLs over time [25] , [51] [53] as well as resulting from actions by enzymes such as phospholipid transfer protein [54] , lecithin:cholesterol acyltransferase [55] , and cholesteryl ester transfer protein [56] . Although anticipated based on the observations made with apoA-I, no evidence of the remodeling of apoLp-III based particles has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A number of groups have investigated the spontaneous remodeling of apoA-I-based rHDLs over time [25] , [51] [53] as well as resulting from actions by enzymes such as phospholipid transfer protein [54] , lecithin:cholesterol acyltransferase [55] , and cholesteryl ester transfer protein [56] . Although anticipated based on the observations made with apoA-I, no evidence of the remodeling of apoLp-III based particles has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Structural stability is essential for HDL functions in lipid transport and metabolism and in the pathogenesis of atherosclerosis and hypertriglyceridemia (9), yet molecular mechanisms of lipoprotein stabilization are not clearly understood. Most existing reports on lipoprotein stability are based upon the equilibrium thermodynamic approach (for recent reviews see refs [9][10][11][12][13][14][15]. However, our recent analyses of model discoidal HDL (16) and spherical human plasma HDL (17), supported by several earlier studies (18)(19)(20), have shown that, contrary to the widely held assumption, HDL stability has a kinetic rather than a thermodynamic origin.…”
mentioning
confidence: 82%
“…Although a reasonable fit is achieved, this model under-predicts association at low protein concentrations and overpredicts it at higher concentrations. The second model is empirical and assumes that tetramer formation is represented by: (4) while keeping the same expression as before for the formation of hexamer. Accordingly, we have:…”
Section: Mass Fraction Of Oligomers = (3)mentioning
confidence: 99%
“…Apolipoprotein A-I is a physiologically important, lipid-binding protein that is the major protein constituent of high density lipoprotein (HDL) involved in cholesterol transport [1][2][3]. It is comprised of a single chain of 243 amino acids with 8 repeating sequences of 22 amino acids forming amphipathic αhelices and 2 tandem repeats of 11 amino acids that enable the protein to bind lipids [3].Apolipoprotein A-I Milano (apoA-I M ) is a naturally occurring variant of apolipoprotein A-I with a cysteine substituted for arginine at position 173 [3][4][5]. When oxidized, apoA-I M consists of a homodimer, with a disulfide bridge connecting two monomers, which reversibly self-associates to higher order species.…”
Section: Introductionmentioning
confidence: 99%